2022
DOI: 10.1093/eurheartj/ehac496
|View full text |Cite
|
Sign up to set email alerts
|

Device-related complications in subcutaneous versus transvenous ICD: a secondary analysis of the PRAETORIAN trial

Abstract: Background The subcutaneous ICD (S-ICD) is developed to overcome lead-related complications and systemic infections, inherent to transvenous ICD (TV-ICD) therapy. The PRAETORIAN trial demonstrated that the S-ICD is non-inferior to the TV-ICD with regard to the combined primary endpoint of inappropriate shocks and complications. This prespecified secondary analysis evaluates all complications in the PRAETORIAN trial. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“… 5 Although there was no significant difference between S-ICD and transvenous ICD in overall device-related complications in the PRAETORIAN trial, 5 a recent secondary analysis showed that complications in the transvenous ICD group were more severe as they required significantly more often an invasive intervention. 16 The present analysis revealed a decrease in the rate of complications from 4.6% in the SC group to 1.0% in the IM group, demonstrating an even better safety profile of the S-ICD when new implantation techniques are adopted. The components that seem to have determined this result are a lower need for reinterventions aimed at improving defibrillation efficacy and shock impedance and fewer revisions for pocket infections or patient discomfort, in agreement with preliminary findings on the benefits of the IM technique for implantation of the S-ICD.…”
Section: Discussionsupporting
confidence: 54%
“… 5 Although there was no significant difference between S-ICD and transvenous ICD in overall device-related complications in the PRAETORIAN trial, 5 a recent secondary analysis showed that complications in the transvenous ICD group were more severe as they required significantly more often an invasive intervention. 16 The present analysis revealed a decrease in the rate of complications from 4.6% in the SC group to 1.0% in the IM group, demonstrating an even better safety profile of the S-ICD when new implantation techniques are adopted. The components that seem to have determined this result are a lower need for reinterventions aimed at improving defibrillation efficacy and shock impedance and fewer revisions for pocket infections or patient discomfort, in agreement with preliminary findings on the benefits of the IM technique for implantation of the S-ICD.…”
Section: Discussionsupporting
confidence: 54%
“…Safety and efficacy at up to 5 years follow-up have been demonstrated in large registries [10,11]. In a previous RCT, the S-ICD was proven non-inferior to the transvenous ICD with respect to all device-related complications over more than 4 years of follow-up, with fewer lead-related complications and systemic infections [5,12]. The LP is a miniaturised pacemaker implanted via the femoral (or jugular) vein that is fully contained within in the heart.…”
Section: The Era Of Extravascular Devicesmentioning
confidence: 98%
“…59 In a subanalysis from the PRAETORIAN randomized controlled study (A Prospective, Randomized Comparison of Subcutaneous and Transvenous Implantable Cardioverter Defibrillator Therapy), the S-ICD had a lower rate of lead-related complications and systemic infections compared with the transvenous ICD. 60 Likewise, the ATLAS trial (Assessment of Treatment with Lisinopril and Survival) showed a lower rate of lead-related complications, including infections with the S-ICD compared with transvenous ICD. 67 Implantation of a S-ICD may be considered among patients with ICD indications with high risk of infection (ie, previous CIED infection or IE, hemodialysis-dependent kidney disease, immunocompromisation, and congenital heart disease 68 ).…”
Section: Managementmentioning
confidence: 99%